Human Clostridium difficile infection caused by a livestock-associated PCR ribotype 237 strain in Western Australia - Mc Govern, Alan M. (JMM Case Rep, 2016)
INTRODUCTION: Clostridium difficile infection (CDI) is a significant gastrointestinal disease in the developed world and increasingly recognised as a zoonotic infection. In North America and Europe, the PCR ribotype (RT) 078 strain of C. difficile is commonly found in production animals and as a cause of disease in humans although proof of transmission from animals is lacking. This strain is absent in Australian livestock. We report a case of human CDI caused by a strain of C. difficile belonging to known Australian livestock-associated RT 237. CASE PRESENTATION: A young male was admitted for multiple trauma following a motor vehicle accident and placed on piperacillin/tazobactam for pneumonia. After 4 days of treatment, he developed symptoms of CDI, which was confirmed in the laboratory. His symptoms resolved after 6 days of intravenous metronidazole. The strain of C. difficile isolated was identified as RT 237, an unusual RT previously found in with several Western Australia piggeries. CONCLUSION: This case of CDI caused by an unusual livestock-associated C. difficile RT 237 supports the hypothesis of zoonotic transmission. The case highlights the potential of livestock to act as reservoir for C. difficile and the need for continued surveillance of CDI in both human and animal populations.